Taking off the training wheels: Measuring auditory P3 during outdoor cycling using an active wet EEG system - Scanlon, Joanna E.M.; Townsend, Kimberley A.; Cormier, Danielle L.; Kuziek, Jonathan W.P.; Mathewson, Kyle E. (Brain research, 2019)
•A backpack containing equipment necessary to record EEG was worn as participants rode a bicycle outside.•EEG data from an auditory oddball task compared with data acquired within-subject inside the lab.•Reliable MMN/N2b and P3 responses measured during bicycle riding outside equal in magnitude to those obtained inside the lab.•Surprising decrease in the P2 component of the ERP evoked by targets and standards observed when doing the task outside on a bicycle. Mobile EEG allows the investigation of brain activity in increasingly complex environments. In this study, EEG equipment was adapted for use and transportation in a backpack while cycling. Participants performed an auditory oddball task while cycling outside and sitting in an isolated chamber inside the lab. Cycling increased EEG noise and marginally diminished alpha amplitude. However, this increased noise did not influence the ability to measure reliable event related potentials (ERP). The P3 was similar in topography, and morphology when outside on the bike, with a lower amplitude in the outside cycling condition. There was only a minor decrease in the statistical power to measure reliable ERP effects. Unexpectedly, when biking outside significantly decreased P2 and increased N1 amplitude were observed when evoked by both standards and targets compared with sitting in the lab. This may be due to attentional processes filtering the overlapping sounds between the tones used and similar environmental frequencies. This study established methods for mobile recording of ERP signals. Future directions include investigating auditory P2 filtering inside the laboratory.